Ready-to-Eat Food as Sources of Extended-Spectrum β-Lactamase-Producing Salmonella and E. coli in Tamale, Ghana - Karikari, Akosua Bonsu; Kpordze, Stephen Wilson; Yamik, David Yembilla; Saba, Courage Kosi Setsoafia (Frontiers in Tropical Diseases, 2022)
The existence of antimicrobial-resistant pathogens in ready-to-eat food is an emerging public health concern. We evaluated the presence of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli and Salmonella species in street food in Tamale, as well as their antibiotic resistance profiles. Samples (42 salad samples and 71 fufu samples) purchased from 113 food vendors in the metropolis were analyzed by selective enrichment and plated onto chromogenic media. The Kirby–Bauer disk diffusion method was used to determine the susceptibility to antibiotics and phenotypic ESBL production. Positive phenotypic analysis for ESBL production was shown in 55.4% (41/74) of E. coli and 44.6% (33/74) of Salmonella species. Antibiotic resistance characterization showed that ESBL strains from salad were completely sensitive to imipenem and chloramphenicol but mostly resistant to cefotaxime (70.0%), ceftriaxone (85.0%), and ceftazidime (70.0%). Nonetheless, 24.1% of ESBL strains from fufu were resistant to imipenem and least resistant to gentamicin (3.7%). In-vitro, E. coli were highly susceptible to ciprofloxacin, gentamicin, and erythromycin, as Salmonella species were more sensitive to imipenem and chloramphenicol; but in both species, resistance to β-lactam drugs was most prevalent. Multiple drug resistance was found in the entire ESBL strains of E. coli and Salmonella species (100%) with respective multiple antibiotic resistance (MAR) indices of 0.56 and 0.48 presented by E. coli and Salmonella species. Our study demonstrated the occurrence of ESBL-producing pathogens in vegetable salads and fufu. The existence of pathogenic bacteria in food is a public health threat and becomes more alarming when the pathogens are endowed with resistant features; thus, policies to combat antimicrobial resistance should be implemented and food safety prioritized.